Book review: Decolonization and Feminisms in Global Teaching and Learning, edited by Sara de Jong, Rosalba Icaza, and Olivia U. Rutazibwa - Joséphine Foucher (University of Johannesburg, 2020)
In this review of Decolonization and Feminisms in Global Teaching and Learning edited by Sara de Jong, Rosalba Icaza and Olivia U. Rutazibwa, book reviewer Joséphine Foucher explains how this book serves as a compelling resource and toolbox for adopting decolonial and feminist thought in the development of critical pedagogies. Keywords: Decolonization, Feminisms, Epistemic justice, Praxis, Critical pedagogy How to cite this article: Foucher, J. 2020. Book review: Decolonization and Feminisms in Global Teaching and Learning, edited by Sara de Jong, Rosalba Icaza, and Olivia U. Rutazibwa. Scholarship of Teaching and Learning in the South. 4(2): 235-238. https://doi.org/10.36615/sotls.v4i2.146. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/